Kualitas Layanan, Kepercayaan Merek dan Kepuasan Penumpang - Simon Gultom; Devi Marlita; Aditya Wardana (Institut Transportasi dan Logistik Trisakti, 2018)
The study aimed at analyzing the data and information about the effect of service quality and brand trust of Garuda Indonesia to the passengers’ satisfaction and retention. The method used was descriptive and associative. The path analysis was used to analyse the data. The primary data was taken from 245 passengers who have been flying with Garuda Indonesia at least 1 time. The survey was conducted in DKI Jakarta. The result shows that the quality of service and the trusted brand effect simultaneously and partially to the passengers’ satisfaction while those three factors effect simultaneously and partially to the passengers’ retention